BAD2matrix: Phylogenomic matrix concatenation, indel coding, and more - Nelson R. Salinas; Gil Eshel; Gloria M. Coruzzi; Rob DeSalle; Michael Tessler; Damon P. Little (Applications in Plant Sciences, 2024)
Abstract Premise Common steps in phylogenomic matrix production include biological sequence concatenation, morphological data concatenation, insertion/deletion (indel) coding, gene content (presence/absence) coding, removing uninformative characters for parsimony analysis, recording with reduced amino acid alphabets, and occupancy filtering. Existing software does not accomplish these tasks on a phylogenomic scale using a single program. Methods and Results BAD2matrix is a Python script that performs the above‐mentioned steps in phylogenomic matrix construction for DNA or amino acid sequences as well as morphological data. The script works in UNIX‐like environments (e.g., LINUX, MacOS, Windows Subsystem for LINUX). Conclusions BAD2matrix helps simplify phylogenomic pipelines and can be downloaded from https://github.com/dpl10/BAD2matrix/tree/master under a GNU General Public License v2.